Kosmologi Dayak dan Spiritualitas Kristen: Inkulturasi Tradisi Munjong ke dalam Ajaran Gereja Katolik pada Masyarakat Dayak Tobak - Paula Leony Putri Terigas; Tjang, Yanto Sandy; Yusmanto Yusmanto; Felisitas Yuswanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study examines the relationship between Dayak cosmology and Christian spirituality through the inculturation of the Munjong tradition within Catholic Dayak Tobak communities in Dusun Batu Besi, Desa Sejotang, West Kalimantan. As a post-harvest thanksgiving ritual, Munjong embodies a symbolic framework reflecting the interconnectedness of humans, nature, ancestors, and Jebata within the Dayak worldview. The tradition functions not only as a religious expression but also as a means of preserving cultural identity and fostering social cohesion. Within a predominantly Catholic context, Munjong has undergone reinterpretation, aligning with Eucharistic spirituality as the Church’s central expression of gratitude. Using a descriptive-qualitative approach combined with symbolic interaction analysis, this study shows that the religious values embedded in Munjong, including: gratitude, petitions for protection, and veneration of ancestors as spiritual mediators, correspond with Catholic teachings on divine providence, the communion of saints, and the sacredness of creation. The local Church recognizes Munjong as a cultural practice suitable for inculturation, provided it aligns with Christian doctrine, thereby offering opportunities for contextual liturgy and catechesis. The findings suggest that Munjong can serve as a bridge between faith and local culture while simultaneously reinforcing cultural identity and deepening the spiritual life of the community. The result of this study contributes to the discourse on inculturation, contextual pastoral practice, and strategies for sustaining indigenous traditions amid social change.